Pembersihan Isi Sel Akar dan Jenis Warna Tinta untuk Deteksi Cendawan Mikoriza Arbuskula: Clearing of Root Cell Content and Types of Ink Stain for Arbuscular Mycorrhizal Fungal Detection - Sulfiah, Siti; Sukarno, Nampiah; Gunawan, Agustin Wydia (Jurnal Sumberdaya Hayati, 2021)
Arbuscular mycorrhizal (AM) fungi form mutualistic symbiosis with root of host plant. Staining technique to detect AM fungi usually used hazardous chemical. The ink stain and vinegar were used as an alternative technique to replace trypan blue and lactic acid in root staining method. This study aimed to determine time for clearing root cell contents and ink stain type to visualize the best AM fungal structures within the root observed under light microscope. Pueraria phaseoloides var. javanica roots colonized by AM fungi were cut into 1 cm long, cleared in KOH solution and stained. Four clearing time were done vis 5, 10, 15 and 20 minutes, and four stains were used namely Shaeffer black ink, Parker Quink blue ink, blue stamp ink, and trypan blue. Twenty stained roots were taken randomly from each tratment, and observed. Root clearing process for 20 minutes showed the best result. Only Shaeffer black ink and trypan blue produced clear structure of external hyphae, internal hyphae, vesicles and arbuscules. Arbuscular structure stained only by Shaeffer black ink and trypan blue. This indicated that Shaeffer black ink could be used as an alternative stain to detect AM fungi within the root of host plant